Art therapy for schizophrenia or schizophrenia-like illnesses. - Ruddy R; Milnes D (Cochrane Database of Systematic Reviews, 2003)
BACKGROUND: Medication is the mainstay of treatment for schizophrenia or schizophrenia-like illnesses. Many people, however, continue to experience symptoms in spite of medication. In addition to medication, creative therapies, such as art therapy may be helpful. Art therapy allows exploration of the patient's inner world in a non-threatening way through a therapeutic relationship and the use of art materials. It was mainly developed in adult psychiatric inpatient units and was designed for use with people in whom verbal psychotherapy would be impossible. OBJECTIVES: To review the effects of art therapy as an adjunctive treatment for schizophrenia compared with standard care and other psychosocial interventions. SEARCH STRATEGY: We searched the Cochrane Schizophrenia Group's Register (May 2002), hand searched reference lists and 'Inscape' (the Journal of the British Association of Art Therapists), and contacted relevant authors. SELECTION CRITERIA: All randomised controlled trials that compared art therapy with standard care or other psychosocial interventions for schizophrenia. DATA COLLECTION AND ANALYSIS: Studies were reliably selected, quality assessed and data extracted. Data were excluded where more than 50% of participants in any group were lost to follow up. For binary outcomes we calculated a fixed effects risk ratio (RR) and its 95% confidence interval (CI). MAIN RESULTS: The search identified 57 reports but only two studies (total n=137) met the inclusion criteria. Both compared art therapy plus standard care with standard care alone. Fewer people allocated to art therapy left the study before 20 weeks compared with those given standard care alone (n=47, 1 RCT, RR 0.34 CI 0.15 to 0.8, NNT 3 CI 1.5 to 7). Measures of change in mental state, interpersonal relationships and social networking were reported but the data were too problematic to interpret with confidence. Much data was lost due to poor reporting or inappropriate use of scales. REVIEWER'S CONCLUSIONS: Randomised studies have been proven to be possible in this field. The use of art therapy for serious mental illnesses should continue to be under evaluation as its benefits, or harms, are unclear.